Analisis Risiko Kesehatan Lingkungan Bahaya Kandungan Logam Berat pada Produk Olahan Pterygoplichthys Pardalis Asal Sungai Ciliwung Jakarta bagi Kesehatan Manusia - Andriani, Rima; Dhefiana, Tika; Surianto, Heri; Sediotono, Blego (Poltekkes Kemenkes Padang, 2025)
Environmental pollution by heavy metals, particularly lead (Pb), has become a major global concern due to its harmful impacts on human health and aquatic ecosystems. This study aimed to analyze the health risks associated with the consumption of processed products made from Pterygoplichthys pardalis (suckermouth catfish) caught in the Ciliwung River, Jakarta, which were found to contain Pb exceeding the permissible limits. An observational design with an Environmental Health Risk Assessment (EHRA) approach was applied. Processed food samples in the form of shredded fish (abon) were analyzed using the X-Ray Fluorescence (XRF) method to measure Pb concentration, followed by intake and Risk Quotient (RQ) calculations. The results revealed that Pb levels in shredded fish reached 1.3 mg/kg, significantly higher than the Indonesian National Standard (SNI) maximum limit of 0.03 mg/kg. The risk assessment showed RQ values of 17.4 for 5 years of exposure, 34.2 for 10 years, and 51.4 for 15 years, all exceeding the safe threshold (RQ > 1). These findings indicate a significant non-carcinogenic health risk, particularly affecting the nervous, renal, and cardiovascular systems if the product is consumed continuously. It can be concluded that processed P. pardalis products from the Ciliwung River are not safe for consumption due to the potential for lead toxicity in the long term. Therefore, strict monitoring of food raw materials from polluted waters, public education on heavy metal hazards